Kewajiban Pajak Pendapatan Yang Harus Dipenuhi Oleh Individu Yang Melakukan Perjalanan Ke Luar Negeri - Burhamzah, Rahmat; Syahrul, Khaidir; Rauf, Deddy Ibrahim (PT Maju Malaqbi Makkarana, 2024)
This discussion is related to Foreign Fiscal policy, which is defined by the tax law that regulates indigenous communities undertaking foreign visits. Initially, the law was more administrative in nature, but over time, it became a source of state revenue. Levies paid by taxpayers while abroad are levies that must be paid during the moving season and can be deducted from income tax at the end of the season. However, according to state inspections, social, cultural, guidance, religion, and universal leadership, except for taxpayers who travel abroad and pay PPh Section 25, for various reasons they may not pay PPh Section 25 while living abroad. country.